Vilnius University Professor Anton Antonovich: Towards the 50-year Anniversary of the Publication of the Pioneer Work “Belorussian Texts Written with the Arabic Script and their Graphic-Orthographic System” (1968) - Мишкинене, Галина (Slavistica Vilnensis, 2018)
[text in Russian]
Keywords: none